Agroecological Social Tissue and Local Development in Ecuador: COVID-19 Framework - Useche Aguirre, María Cristina (2021)
The multidimensional crisis that Ecuador has experienced as a result of the COVID-19 coronavirus since the year 2020 had an impact on agroecological activity and the people involved in it as well, which motivated us to describe the agroecological social tissue in the province of Azuay in Ecuador, in the framework of local development in times of COVID-19. As this is empirical research, a field research type was used with the participation of 498 agroecological associations as the study population, from which a sample of 116 associations was drawn, which collaborated in the collection of information by responding to a structured questionnaire. It is concluded that the social tissue is made up of macro and micro social links that converge in the socio-ecological system of agroecology in four subsystems: socio-cultural, socio-political, eco-structural, and eco-economic, to contribute to local development and meet both the economic and health needs of the social actors in agroecology in the face of the pandemic in the aforementioned country.KEYWORDS: Social behavior, local development, Ecuador, human ecology, social systems.